Prioritising SDG targets: assessing baselines, gaps and interlinkages - Allen, Cameron; Metternicht, Graciela; Wiedmann, Thomas (Sustainability science, 2019)
The sustainable development goals (SDGs) provide an integrated, evidence-based framework of targets and indicators to support national planning and reporting. For countries to begin implementation of the SDGs, it is critical to build the evidence base for action. The integrated nature of the SDG targets mean that progress towards one target is also linked through complex feedbacks to other targets, placing demands on science and research to support national implementation. A range of different tools and approaches are recommended by experts, and an emerging challenge is to coherently apply and combine these different approaches to support decision-making. This study makes a significant contribution to filling this knowledge gap, adopting a novel integrated assessment approach to support the prioritisation of SDG targets through a case study for 22 countries in the Arab region. The research adopts a multi-criteria analysis decision framework which assesses and prioritises SDG targets based upon their ‘level of urgency’, ‘systemic impact’, and ‘policy gap’. A range of complementary evidence- and science-based approaches are applied within the assessment framework, including baseline assessment and benchmarking of indicators, systems and network analysis of target interlinkages, and mapping of policy alignment and gaps. The study highlights the strengths and weaknesses of each of these analytical approaches, and demonstrates how they can be rapidly combined and applied.